Environmental Kuznets curve estimation for NO2 emission: A case of Indian cities. (August 2016) - Sinha, Avik; Bhattacharya, Joysankar
Highlights: We have estimated environmental Kuznets curve (EKC) for 139 Indian cities considering NO2 emissions. Study has been done for 2001–2013, and the data have been segregated by residential and industrial areas, and as well as low, medium, and high income areas. Fixed and random effect panel regressions have been used for analysis. By virtue of different forms of EKC being found, policy level decisions have been designed. Non-rejection of EKC hypothesis reemphasized the impact of growth catalyzing economic policy decisions on environment. Abstract: Interaction between environmental degradation and economic growth is a growing matter of interest among policymakers. Here we have estimated environmental Kuznets curve (EKC) for 139 Indian cities considering NO2 emissions. Study has been done for 2001–2013, and the data have been segregated by residential and industrial areas, and as well as low, medium, and high income areas. By virtue of different forms of EKC being found, policy level decisions have been designed. Moreover, non-rejection of EKC hypothesis reemphasized the impact of growth catalyzing economic policy decisions on environment.